Profile of maternal mortality in the State of Ceará - Lucélia Rodrigues Afonso; Victor Hugo Santos de Castro; Cláudia Patrícia da Silva Ribeiro Menezes; Lívia Lopes Custódio; Marcelo Gurgel Carlos da Silva; Ilvana Lima Verde Gomes (Instituto Materno Infantil de Pernambuco, 2022)
Abstract Objectives: evaluate maternal mortality from January 2019 to January 2020 in the state of Ceará. Methods: this is a descriptive and retrospective ecological study. Data collection was carried out from October to November 2020, considering the time interval from January 2019 to January 2020, through information registered in a public domain database in the State of Ceará, Brazil. The variables considered to outline the profile of maternal deaths were: age group, causes, marital status, color/race and education. Data analysis was performed using descriptive statistics by frequency distribution and presented through tables. Results: 135 maternal deaths were registered, considering external, direct (most prevalent), indirect and late causes. The maternal mortality ratio in Ceará was 60.43%, whose profile of deaths was characterized by women with incomplete higher education (41.5%), brown (80%), in their 20-29 years (43%) and single (66.7%). Conclusion: the information in this study is extremely importance, as it allows the understanding of a key population, women, in addition to assisting in the design of strategies for coping with maternal mortality.